PENGARUH PENGGUNAAN UANG DIGITAL TERHADAP PERILAKU KONSUMTIF DAN GAYA HIDUP MASYARAKAT - Alief Hidayatullah, Mohammad; Nurul Jipri, Moh. Amin; Hartono, Rudi; Santoso, Urip; Nanda Putra Afnany, Moch. Rifqi (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) IBE Indonesia, 2024)
Consumer behavior in the current era comes from the process and not from oneself because it follows developments in increasingly modern times. The phenomenon that occurs in the people of Talkandang Village, Kotaanyar District, Probolinggo Regency also reflects the consumptive behavior that occurs in society which can be seen from the behavior of using goods that are trendy and have high purchasing prices. This research is to examine the influence of the use of Digital Money on consumer behavior and lifestyle of the people of Talkandang Village, Kotaanyar District. This research uses a quantitative approach in the form of primary data obtained from distributing questionnaires and then processing the data using SPSS 25. The population of this research is 4980 people with a sample of 347 respondents. From the research results, it is known that the use of digital money has a positive and significant effect on student consumptive behavior. Meanwhile, the use of Digital Money does not have a positive or significant impact on people's lifestyles.